Masking ability of CAD-CAM resin-matrix ceramics with different translucencies and thicknesses combined with four cement shades against varying background colors when facing veneer restorations - Jiakang Zhu; Yanlin Xia; SiIn Lui; Wenxiang Wang; Shanshan Liang; Cui Huang (BMC, 2024)
Abstract Background To evaluate the comprehensive effect of translucency, thickness, cement shades, and background color on the masking ability of resin-matrix ceramic veneer restorations. Methods Resin-matrix ceramic specimens with 2 translucencies (LT, HT) and 3 thicknesses (0.5, 1.0, and 1.5 mm) were made of Upcera Hyramic (A2 shade). Cement specimens were made of Variolink N in 4 shades (yellow, white, transparent, and bleach XL). Five background specimens were made of IPS Natural Die Material in 5 shades (ND1, ND2, ND3, ND4, and ND5). Color coordinates of 120 subgroups (n = 5) of combined specimens composed of different ceramic, cement, and background specimens were obtained using a spectroradiometer. Color difference (ΔE00) compared with a 4-mm thick specimen of LT and HT ceramics was calculated and four-way ANOVA was used for statistical analysis (α = 0.05). Results Translucency, thickness, cement shade, background color, and their interaction had significant effects on ΔE00 (p < 0.001). ΔE00 values of HT groups were always higher than that of LT groups and were greater than 1.8 against all background colors. ΔE00 values of LT groups could be achieved to be less than 1.8 with appropriate thickness and cement shade. ΔE00 value decreased with increasing ceramic thickness. The effect of cement shade on ΔE00 had no obvious regularity, but ΔE00 values of bleach XL cement shade group were always lower than other cement shade groups under ND3 and ND5 background color. Conclusions The masking ability of CAD-CAM resin-matrix ceramics can be simultaneously affected by translucency, thickness, cement shade, and background color. Resin-matrix ceramics with low translucency has a better masking ability than that with high translucency. The masking ability of CAD-CAM resin-matrix ceramics increase with increasing thickness. Cement shade has less impact on the final color of resin-matrix ceramic restorations.